2018
DOI: 10.5114/ppn.2018.77033
|View full text |Cite
|
Sign up to set email alerts
|

Components of emotion dysregulation in borderline personality disorder: A review of recent research

Abstract: Purpose: The aim of this paper is a synthetic presentation of the latest research results on the components of emotion dysregulation in borderline personality disorder (BPD). Views: Emotion dysregulation constitutes one of the most serious problems in BPD and manifests itself in numerous aspects of emotional functioning. Studies on BPD emotion dysregulation concern its various components, distinguished in different theoretical models. Based on a review of the empirical literature, we differentiate three main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…With respect to habitual or preferred ER strategy use, participants with BPD typically reported lower use of adaptive (e.g., cognitive reappraisal and mindfulness) and greater use of maladaptive (e.g., experiential avoidance and self-criticism) ER strategies relative to HCs, consistent with previous reviews (e.g., Carpenter & Trull, 2013;Gratz et al, 2018;Grzegorzewski & Kucharska, 2018). However, some findings deviated from this trend, with differences in certain ER strategies garnering more support than others.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…With respect to habitual or preferred ER strategy use, participants with BPD typically reported lower use of adaptive (e.g., cognitive reappraisal and mindfulness) and greater use of maladaptive (e.g., experiential avoidance and self-criticism) ER strategies relative to HCs, consistent with previous reviews (e.g., Carpenter & Trull, 2013;Gratz et al, 2018;Grzegorzewski & Kucharska, 2018). However, some findings deviated from this trend, with differences in certain ER strategies garnering more support than others.…”
Section: Discussionsupporting
confidence: 82%
“…Several review articles on ER in BPD have included some studies of ER strategies, finding that BPD is associated with greater use of maladaptive strategies such as rumination, experiential avoidance, and thought suppression and less frequent use of adaptive strategies such as distraction and cognitive reappraisal (Carpenter & Trull, 2013; Cavicchioli et al, 2015; Chapman et al, 2011; Gratz et al, 2018; Grzegorzewski & Kucharska, 2018; Jazaieri et al, 2013). However, the majority of these were not systematic, comprehensive reviews of the literature on ER strategy use in BPD but rather included a nondescript sampling of ER strategy studies within a broader discussion of ER deficits in BPD (Carpenter & Trull, 2013; Gratz et al, 2018; Grzegorzewski & Kucharska, 2018; Jazaieri et al, 2013) or discussed the theorized role of one particular strategy (i.e., experiential avoidance) in BPD (Chapman et al, 2011). More recently, a meta‐analytic review (conducted in 2016) of 93 studies of ER strategies in relation to BPD symptoms showed that BPD symptoms were associated positively with the use of three maladaptive (i.e., rumination, suppression, and avoidance) and negatively with three adaptive (i.e., cognitive reappraisal, acceptance, and problem‐solving) ER strategies (Daros & Williams, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, components of emotion dynamics, such as emotional interdependency across time, emotional dialecticism (bipolarity), emodiversity and other subtypes of emotional lability, including the probability of acute change or emotional switching (for overviews, see [ 10 , 65 , 66 ]), as well as cognitive ER strategies, for example cognitive reappraisal or distraction, and behavioural ER strategies, such as social support seeking (for overviews, see [ 67 , 68 ]) should be examined. In addition, patients with AN need to be compared to patients with other mental disorders characterised by maladaptive emotion dynamics and ER, such as borderline personality disorder [ 69 ] or major depressive disorder [ 70 ], in order to identify disorder-specific and transdiagnostic patterns of these phenomena. Given disordered ER in men with AN see [ 71 ], this group should also be involved in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers underline the problem of inappropriate emotion regulation characteristic for people with personality disorders, especially in case of borderline personality disorder (Cavicchioli et al, 2021), but emotional crises are observed in other mental disorders as well (Santangelo et al 2016). Persons suffering from difficulties associated with personality disorders experience very complex emotional dysregulation resulting from biological and environmental causes (Grzegorzewski & Kucharska, 2018). They encounter a high level of emotional sensitivity, and a high level of emotional reactivity accompanied by a low level of agility of nervous processes.…”
Section: Relationships and Attachmentmentioning
confidence: 99%